Задачи равновесия для потенциалов с внешними полями - Зорий, Н.В. (Український математичний журнал, 2003)
Досліджується задача про мінімум енергії при наявності зовнішніх полів над вельми загальними (взагалі кажучи, некомпактними) класами дійсних мір Радона, асоційованих з системою множин в локально компактному просторі. Класи допустимих мір задаються через певне нормування або ж через нормування та деяку мажорантну міру σ. В обох постановках знайдено достатні умови існування мінімізуючих мір та доведено, що при досить широких припущеннях вони є одночасно і необхідними. Показано, що між явищами нерозв'язності (чи розв'язності) відповідних варіаційних задач при досить великих σ існує тісний взаємозв'язок. We investigate the problem on the minimum of energy over fairly general (generally speaking, noncompact) classes of real-valued Radon measures associated with a system of sets in a locally compact space in the presence of external fields. The classes of admissible measures are determined by a certain normalization or by a normalization and a certain majorant measure σ. In both cases, we establish sufficient conditions for the existence of minimizing measures and prove that, under fairly general assumptions, these conditions are also necessary. We show that, for sufficiently large σ, there is a close correlation between the facts of unsolvability (or solvability) of both variational problems considered.